O Conceito De Idolatria Do Mercado No Pensamento De Hugo Assmann - Santos, Thales Martins dos (2023)
This research aims at approaching the critique of the idolatry of the neoliberal market in Hugo Assmann’s thought. The author assumes theology as a struggle in favor of real and concrete human life and, therefore, his investigation consists of recognizing the idols in different theologies who are in opposition to the God of Life. Thus, Hugo Assmann criticizes neoliberalism as a theory that absolutizes the Market and makes it the ultimate principle of society. Therefore, when it promotes the sacrifice of innocent victims in the neoliberal system, the Market opposes the God of Life and, hence, is considered an idol. In order to demonstrate this itinerary, first, we propose to situate Hugo Assmann's thought departing from the Latin American reality, especially with the poor, and also in dialogue with liberation theology and the Ecumenical Department of Investigations. Second, it is necessary to understand the discussion on theology and economics from Assmann’s thought, and the development of this debate from neoliberalism, demonstrating its process of transcendentalization and idolatry. Finally, it is important to explain that Assmann does not criticize the market itself, but its absolutization, and also to point out the clues the author leaves for the relationship between economics and theology.(AU)